Left ventricular non-compaction presenting with heart failure and intramural thrombus. (12th July 2013) - Aryal, Madan Raj; Badal, Madan; Giri, Smith; Pradhan, Rajesh
Abstract : Left ventricular non-compaction (LVNC) is a rare disorder caused by the arrest of myocardial compaction during embryogenesis, leading to a non-compacted endocardial layer with marked trabeculations. The diagnosis is primarily based on echocardiographic demonstration of a spongy myocardium. Here, we present a young male with LVNC presenting with left heart failure and multiple left ventricular thrombi. We also review the presentation, diagnosis and management of this condition.